Efektivitas Baamboozle terhadap Kemampuan Memahami Teks Cerita Rakyat Sumatera Utara pada Siswa Kelas VII SMP - Kusyani, Diah; Adelina Ray, Sukma (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study was to determine the effectiveness of bamboozle in learning to understand North Sumatra folklore text in junior high school. This research is an experimental research with one-group pretest-posttest research design. The results of the study concluded that understanding the text of North Sumatra folklore using bamboozle by students of class VII-1 SMP Negeri 1 Delitua obtained an average score of 83.61 while if understanding the text of North Sumatra folklore without using bamboozle by students of class VII-3 SMP Negeri 1 Delitua obtained an average score of 73.12. The bamboozle application is effective in understanding the text of North Sumatra folklore. Significant in this study is 0.001 <0.05 which means Ho is rejected and Ha is accepted, meaning that the bamboozle application is effective to improve students’ understanding of folklore text. In this study, there is a significant difference in using bamboozle and without using bamboozle on the ability to understand folklore text by students of class VII-1 and VII-3 SMP Negeri 1 Delitua, namely bamboozle is declared effective in learning to understand folklore text and makes students more enthusiastic in the learning process.